Destination branding wisata Girpasang Klaten dalam membangun brand image sebagai wisata asri - Tyas, Tiara; Fikrani Deslia, Iva (Universitas Garut, 2025)
Girpasang Tourism is a village-based tourism destination located in Girpasang Village, Klaten Regency. This study aims to explore the stages of Destination Branding at Girpasang Tourism in building its brand image as an eco-tourism destination. The research method used is descriptive qualitative, with data collection techniques through interviews, observations, documentation study, and literature review. The research findings indicate that in the Market Investigation and Strategic Analysis stages, Girpasang Tourism conducts a SWOT analysis that highlights its uniqueness as the main strength of the brand, although there are some weaknesses and threats that are not significant. In Brand Identity Development, Girpasang Tourism has a name, logo, and tagline that reflect the image it wishes to project. Brand launching is carried out through social media, mass media, events, and collaborations with influencers. Brand implementation involves the five Pentahelix elements, each contributing according to its respective field. Monitoring, evaluation, and review are conducted continuously, with the management carrying out monthly evaluations to maintain quality and address issues.